The Influence of Islamic Financial Literacy, Halal Lifestyle, and Religiosity on the Intention to Use Sharia Banking Services - Mukhid (International Humanity Advance, Business & Sciences, 2025)
This study explores the influence of Islamic financial literacy, halal lifestyle, and religiosity on the intention to use Sharia banking services among Muslim consumers in Indonesia. As Sharia banking becomes an essential pillar of the Islamic financial system, understanding the behavioral drivers behind its adoption is crucial. The research employed a quantitative approach, surveying 250 respondents using a structured questionnaire. Data were analyzed using SPSS with multiple linear regression analysis. The results revealed that all three independent variables—Islamic financial literacy, halal lifestyle, and religiosity—had a significant and positive impact on the intention to use Sharia banking services. Religiosity emerged as the most dominant factor, underscoring the significant role of spiritual values in shaping financial decision-making. These findings underscore the importance of increasing Islamic financial awareness, promoting a halal-oriented lifestyle, and incorporating religious dimensions into marketing and educational strategies. The study provides both theoretical contributions and practical implications for enhancing the growth and adoption of Sharia-compliant banking in Indonesia.